Development of sugar palm fibre reinforced thermoplastic polyurethane composites - Abbas, Mohammed Ausama Al-Sarraf (2017)
Sugar palm fibre (SPF) has good tensile properties. It is suitable to be used as a reinforcing agent in composite materials. Thermoplastic polyurethane (TPU) is a flexible and expensive polymer, which has a shorter processing time and is lower in energy, tougher, and recyclable. It has excellent abrasion resistance and has good mechanical properties. In contrast, the natural fibre is hydrophilic in nature, whereas most polymers are hydrophobic in nature. To date, very little study about the thermoplastic polyurethane reinforced natural fibre has been investigated. The objective of this study is to develop a new natural fibre (SPF) as a novel utilisation composite thermoplastic polyurethane structure. The synthesis of SPF fibre and TPU was carried out using an extruder and the resulting material was compressed in the mould using compression moulding at 190 °C. The experimental procedure was divided into three parts. First is the preparation of new TPU/SPF composite structures without any changes, then optimising the operation conditions (rotation velocity, the temperature of extrusion, fibre size, and fibre contents) on the final mechanical and the thermal properties. Next, the new assemblies were developed by applying three treatment methods on SPF: chemical NaOH, chemical KMnO4, and physical microwave. Finally, the effects of these methods were studied using tensile strength property and the effect of the treatment methods testing over the behaviour of the final assemblies using characterizations such as thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscope (SEM), energy dispersive X-ray (EDX), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The results indicated that optimum operating conditions obtained experimentally were at 40 rpm min rotation velocity, 190 °C temperature, 250 μm fibre size, and 10 wt. % fibre content. The values of tensile strength, modulus and strain at these conditions were 14.01 MPa, 23.34 MPa, and 253.186 % respectively. The flexural strength and modulus values were at 11.162 MPa and 145.252 MPa. In addition, the impact strength was at 100.2 kJ/m2. Higher tensile strength was obtained for NaOH treatment method with the effective concentration of 6 %, followed by higher impact strength and tensile strain values as 5.488 MPa, 103.4 kJ/m2, and 48.012 % respectively. Also, the flexural and tensile modulus and flexural strength for 6 % NaOH TPU/SPF values were 293.936 MPa, 30 MPa, and 11.1632 MPa respectively. However, the highest flexural strength was recorded at 2 % NaOH treated TPU/SPF composite value such as 12.606 MPa, while the biggest impact strength of this method was 103.4 kJ/m2 for 6 % NaOH TPU/SPF composites. Higher thermal stability of 17.56 % and decomposition temperature of 372 °C were achieved from 4 % NaOH TPU/SPF treated fibre composite. The activation was then improved by applying a potassium permanganate chemical solution, with enhanced tensile strength, modulus, and strain values at 8.986 MPa, 876.436 MPa, and 1.442 % respectively, for 0.125 KMnO4 and 6 % NaOH pre-treatment TPU/SPF. The same deteriorated effect was observed in the flexural strength, modulus and impact strength values at 4.988 MPa, 180.744 MPa and 53.9914 kJ/m2 respectively, for the KMnO4 treatment method on the TPU/SPF composites due to fibre degradation. TGA analysis SPF treated with 0.033 KMnO4 recorded better thermal stability of 15.23 % and decomposition temperature of 374 °C when compared with 6 % NaOH treated fibre TPU/SPF composites. On the other hand, the physical microwave treatment method vi enhanced further tensile, and flexural, strength and tensile modulus as 18.42 MPa, 13.66 MPa and 1307.562 MPa respectively. However, the impact strength for the microwave method at 70 °C deteriorated at 71.527 kJ/m2. Also, these composites recorded highest thermal stability at 13.47 % and decomposition temperature of 389 °C by TGA analysis when compared with other operating temperatures of microwave treatment. SEM analysis showed that there was a clear effect on the structure of TPU/SPF composites before and after the treatment methods on the fibre. At the same time, the EDX identified residual trace materials deposited on the surface of the composites after the treatment. Meanwhile, the DSC analysis was compatible with the mechanical properties. XRD and FTIR results showed a good agreement with the mechanical characterization of the samples respectively, where the XRD sample of the 70 °C microwave treated fibre gave better results in the tested samples. The TPU/SPF composite which has SPF treated at 70 °C microwave treatment can be considered as a suitable composite material because of it has good mechanical and thermal properties. This is expected for the use of the interior parts in the automotive.